Media and protest logics in the digital era the umbrella movement in Hong Kong - Lee, Francis L.F. 1975-; Chan, Joseph Man (Oxford studies in digital politics, 2018)
For 79 days in 2014, Hong Kong became the focus of international attention due to a public demonstration for genuine democracy that would become known as the Umbrella Movement. On the surface, this movement was not unlike other large-scale protest movements that have occurred in recent years. However, it was distinct in how bottom-up processes evolved into a centrally organized, programmatic movement with concrete policy demands. This book analyzes how traditional mass media institutions and digital media combined with on-the-ground networks in such a way as to propel citizen participation and